Comparative evaluation of microleakage of three restorative glass ionomer cements: An in vitro study - Diwanji, Amish (Medknow Publications & Media Pvt Ltd, 2014)
PURPOSE: The aim of this study was to compare the microleakage of glass ionomers (conventional and resin modified) with that of recently introduced nanoionomers. MATERIALS AND METHODS: Standardized class I and class V cavities were prepared on 120 young permanent teeth. Samples were equally divided into group I (class I restorations) and group II (class V restorations), and further divided into subgroups. The subgroups were restored with Fuji IX, Fuji II LC, and newly introduced Ketac(™) N 100 (KN 100). Samples were thermocycled and submerged in Acridine dye for 24 h. Samples were sectioned to view under fluorescent microscope and marginal leakage was evaluated by Chi-square and Kruskal — Wallis test. RESULTS: Fuji IX showed the maximum leakage, followed by LC II and the least was observed in KN 100. In class I restorations, there was significant difference while comparing Fuji IX with Fuji LC II and KN 100 and nonsignificant difference between LC II and KN100. In class V restorations, Fuji IX and KN100, KN 100 and LC II showed significant difference. Fuji IX and LC II showed nonsignificant difference. CONCLUSION: Within the limitations of this study, Fuji IX showed the maximum microleakage. KN 100 showed minimum leakage, better sealing ability, and was more consistent.